FentAnyl or placebo with KeTamine for emergency department rapid sequence intubation: The FAKT study protocol. Issue 5 (17th January 2019) - Ferguson, Ian; Milligan, James; Buttfield, Alex; Shepherd, Shamus; Burns, Brian; Reid, Cliff; Aneman, Anders; Harris, Ian
Abstract : Background: Some critically ill patients require rapid sequence intubation in the emergency department, and ketamine is one sedative agent employed, due to its relative haemodynamic stability. Tachycardia and hypertension are frequent side effects, and in less stable patients, shock can be unmasked or exacerbated. The use of fentanyl as a co‐induction agent may lead to a smoother haemodynamic profile post‐induction, which may lead to reduced mortality in this critically ill cohort. This randomised controlled trial aims to compare the effect of administering fentanyl vs placebo in a standardised induction regimen with ketamine and rocuronium on (a) the percentage of patients in each group with a systolic blood pressure outside the range of 100‐150 mm Hg within 10 minutes of induction, (b) the laryngoscopic view, and (c) 30‐day mortality. Methods/design: Three hundred patients requiring rapid sequence intubation in participating emergency departments will be randomised to receive either fentanyl or placebo (0.9% saline) in addition to ketamine and rocuronium according to a standardised, weight‐based induction regimen. The primary outcome measure is the percentage of patients in each group with a systolic blood pressure outside the range of 100‐150 mm Hg within 10 minutes of induction. Secondary outcome measures include the laryngoscopic view, percentage of first pass success, 30‐day mortality and number of ventilator‐free days at 30 days. Discussion: The effect of adding fentanyl to an induction regimen of ketamine and rocuronium will be evaluated, both in terms of post‐intubation physiology, the effect on intubating conditions, and 30‐day mortality.